The Expedient of Decreased on The Meat and Blood Cholesterol Concentration Throught Use â€œKayu Apuâ€ (Pistia strtiotes L) in The Local Chicken Feed, Old 3-10 Weeks - Tjokorda Gede Belawa Yadnya; Ni Gusti Ketut Roni; Desak Putu Mas Ari Candrawati; Anak Agung Putu Putra Wibawa (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2010)
The research was carried out to study the effect of kayu apu (Pistia Stratiotes L) in diets of cholesterol concentration in the blood and mea on the chickn local. The experiment was designed using completely randomized design (CRD) with four treatments which were ration withoutâ€ kayu apuâ€(Pistia stratiotes L) as control (P0), ration with 10% kayu apu (P1), ration with 20% kayu apu (P2) and ration with 30% kayu apu (P3). Each treatment group had three replicates with five birds in each replicates. Data observation are total choresterol, low density lipoprotein (LDL), high density lipoprotein (HDL) in the blood and meat cholesterol. The result showed that the offered 10%-30% kayu in diets could be decrease of cholesterol total and Low Density Lipoprotein (LDL) were significanty (P<0,05), but not affected of High Density Lipoprotein (HDL) (P>0,05). The same incident of the offered kayu apu could be decrease of cholesterol concentration total in theÂ  meat. It was included that of kayu apu (Pistia Stratiotes L) 10%-30% in the ration could be increase on feed efficiency, decrease of carcass fat and cholesterol concentration in the blood and meat of the chicken local. Â  Keywords: The expedient of decrease cholesterol, kayu apu (Pistia Stratiotes L) and Chicken local